2016
DOI: 10.1007/s10120-016-0619-z
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of preoperative chemotherapy with docetaxel, cisplatin, and S-1 followed by gastrectomy with D2 plus para-aortic lymph node dissection for gastric cancer with extensive lymph node metastasis: JCOG1002

Abstract: Background Gastric cancer with extensive lymph node metastasis is commonly considered unresectable, with a poor prognosis. We previously reported the results of the use of cisplatin and S-1 as preoperative chemotherapy for gastric cancer with extensive lymph node metastasis; docetaxel, cisplatin, and S-1 (DCS) have now been investigated for the same purpose. Methods Patients received two or three 28-day cycles of DCS therapy (docetaxel at 40 mg/m 2 and cisplatin at 60 mg/m 2 on day 1, S-1 at 40 mg/m 2 twice da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 22 publications
4
100
2
Order By: Relevance
“…JCOG1002 was planned as a phase II trial with the expectation that neoadjuvant DCS would be more effective than neoadjuvant CS in terms of tumor shrinkage. This trial evaluated the efficacy of preoperative chemotherapy for not only bulky N2 lymph node metastasis but also para-aortic lymph node metastasis [13]. Contrary to expectation, the primary endpoint, the clinical RR, was 57.7%, which was lower than the predefined threshold rate of 65%.…”
Section: Discussionmentioning
confidence: 94%
“…JCOG1002 was planned as a phase II trial with the expectation that neoadjuvant DCS would be more effective than neoadjuvant CS in terms of tumor shrinkage. This trial evaluated the efficacy of preoperative chemotherapy for not only bulky N2 lymph node metastasis but also para-aortic lymph node metastasis [13]. Contrary to expectation, the primary endpoint, the clinical RR, was 57.7%, which was lower than the predefined threshold rate of 65%.…”
Section: Discussionmentioning
confidence: 94%
“…However, docetaxel was not included in the present study. We have previously performed a phase II trial investigating the safety and efficacy of preoperative docetaxel plus CDDP plus S-1 (DCS) in patients with extensive nodal disease [24]. The safety was similar to that of SP regimen.…”
Section: Discussionmentioning
confidence: 99%
“…As such, in these stages a multidisciplinary approach is advisable, with possible integrated approach including neoadjuvant treatments or intraperitoneal chemotherapy (56). Recent studies reported very good long-term survival rates in patients with extensive or bulky lymph node metastases submitted to neoadjuvant chemotherapy and D2 plus lymphadenectomy (31,57). This is particularly true in Western series, where the rate of diffuse type tumors, associated with a high propensity to spread to regional and distant nodes, is increasing with time (26,56).…”
Section: Long-term Resultsmentioning
confidence: 99%